A Soli Deo Gloria és a Magyar Testvéri Közösség kapcsolata - Nóra SZEKÉR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
The Relationship between the Soli Deo Gloria Student Association and the Hungarian Fraternal Community.  The Reformed Youth Organization, i.e. the Soli Deo Gloria Student Association, and the Hungarian Fraternal Community were closely related. The Community was a secret organization with an anti-Nazi stance and was dissatisfied with the social system of the Horthy era. Soli Deo Gloria embraced the social problems and opposed Nazism. The common approach has created cooperation. The Hungarian Fraternal Community as a secret organization became the main de-fendant in the Conspiracy Trial of 1947. It was accused of wanting to overthrow the republic and was called a terrorist organization. The presentation of the co-operation between Soli Deo Gloria and the Community aims to reveal the true nature of the latter. The Hungarian Fraternal Community wanted to provide help from the background and not to enforce its will.